2022
DOI: 10.2196/21208
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Health Professionals’ Perceptions on Patient-Controlled Granular Information Sharing (Part 1): Focus Group Study

Abstract: Background Patient-controlled granular information sharing (PC-GIS) allows a patient to select specific health information “granules,” such as diagnoses and medications; choose with whom the information is shared; and decide how the information can be used. Previous studies suggest that health professionals have mixed or concerned opinions about the process and impact of PC-GIS for care and research. Further understanding of behavioral health professionals’ views on PC-GIS are needed for successful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Our results support and expand these findings; namely, the health professionals have defined challenges in PC-GIS implementation (28/35, 79% of final concerned and mixed opinions), attempted to understand patient motivation for redaction, aimed for balance between patient and professionals’ needs, and underscored the need to access necessary health information for successful care delivery (23/39, 60% of all recommendations). The pre- and postsurvey analysis (described separately) [ 28 ] shows significant changes ( P <.05) in health professionals’ opinions toward concern after the focus group [ 30 ]. Our qualitative analysis mirrors and provides insight into the increase of mixed opinions with comprehension of PC-GIS as well as recommendations to mitigate mutual concerns related to PC-GIS and avoid friction in the patient-professional relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support and expand these findings; namely, the health professionals have defined challenges in PC-GIS implementation (28/35, 79% of final concerned and mixed opinions), attempted to understand patient motivation for redaction, aimed for balance between patient and professionals’ needs, and underscored the need to access necessary health information for successful care delivery (23/39, 60% of all recommendations). The pre- and postsurvey analysis (described separately) [ 28 ] shows significant changes ( P <.05) in health professionals’ opinions toward concern after the focus group [ 30 ]. Our qualitative analysis mirrors and provides insight into the increase of mixed opinions with comprehension of PC-GIS as well as recommendations to mitigate mutual concerns related to PC-GIS and avoid friction in the patient-professional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Coding assessments provided qualitative and quantitative insight into participant rationale for PC-GIS opinions with outcomes. Pre- and postsurvey analysis is described in part 1 of this study [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that providers believe patient limits on data access may adversely impact patient care. 11,17,19,20 Ivanova et al interviewed 28 behavioral health providers and professionals to assess their views on patient control of medical record sharing and found that providers' opinions may be impacted by the medical and mental health problems of their patients. 19,20 The study found that behavioral health professionals caring for individuals with a serious mental illness displayed lower levels of data sharing concern and emphasized patient perspectives (63.6%), compared to those caring for individuals with general mental health conditions.…”
Section: Introductionmentioning
confidence: 99%